The impact of the informal economy on R&D, wage inequality and economic growth - Óscar Afonso (2017)
We extend the existing research and development (R&D) growth literature by focusing on the short-medium-long run effects of the informal sector on R&D intensity, wage inequality and economic growth, and by considering 18 OECD countries between 1990 and 2008. We show that: the steady state is unique and stable; the share of informal economy (IE) in production affects negatively R&D intensity and wage equality; Nordic countries have the lowest share of IE in production, while Mediterranean countries have the highest share of IE, wage inequality and R&D intensity but R&D spillovers are lower.